Evaluation and Nonsurgical Treatment of Neonatal Ear Anomalies: A Case Report. (8th August 2022) - Moss, Colleen Reilly; Gargaro, Clare
Abstract : Background: Inspection and evaluation of the neonate's ears are important parts of the neonatal examination. Neonates display a wide variety of ear size and configuration. In many cases, ear molding techniques obviate the need for future surgical correction. This article provides a review of the fetal ear development and describes common physical examination findings of the newborn's external ear. A case report reviews a successful nonsurgical treatment of a minor ear deformity. Clinical Findings: Newborn infant with near absent to very thin bilateral helical rims and otherwise normal bilateral ear shape and structures. Primary Diagnosis: Bilateral Stahl's ear deformity. Interventions: The EarBuddies product was applied to bilateral ears in an outpatient pediatric plastic surgery clinic. This product remained in place for 8 weeks. Outcomes: The family was pleased with the overall progress and shape of their child's ears. At 18 months of age, the family has no desire to pursue surgical correction of their child's ears. Practice Recommendations: Assessment of the newborn's external ear is part of a routine admission examination. Careful attention to abnormal or unusual findings allows for prompt evaluation and nonsurgical intervention.